Representasi Budaya dalam Materi Pembelajaran Bahasa Indonesia Kurikulum Merdeka Tingkat SMA - Miranti, Miranti; Mukodas, Mukodas; Anwar, Miftahulkhairah (Asatiza: Jurnal Pendidikan, 2024)
In the context of the development of the Merdeka Curriculum in Indonesia, this study highlights the importance of understanding how cultural values are reflected in Indonesian language learning at the high school level. The research method used is descriptive using qualitative analysis to explore the integration of local culture and the use of local languages in the “Cerdas Cergas Berbahasa dan Bersastra Indonesia” textbook for grades X, XI, and XII. The findings show that the adoption of folklore, customs and local languages in the curriculum not only enhances students' understanding of Indonesia's cultural heritage, but also provides a rich and meaningful learning experience. As such, this integration provides a strong national identity for students and reinforces a sense of pride in the nation's culture. This research makes an important contribution to understanding how education can be an effective vehicle for enriching and maintaining cultural diversity in Indonesia.